2022
DOI: 10.1155/2022/9459186
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Suicidal Ideation among Almeda Textile Factory Workers in Adwa, Tigray, Ethiopia: A Cross‐Sectional Study

Abstract: Background. Suicidal ideation among textile factory workers is a major public health concern worldwide and is associated with a higher risk of completed suicide. However, there are limited studies that determined the prevalence and the potential determinants of suicidal ideation in Africa, including Ethiopia. Therefore, this study is aimed at exploring the prevalence of suicidal ideation and associated factors among textile factory workers in Almeda textile factory in Adwa, Ethiopia. Methods. An institutional-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Reports showed that industries including the textile sector have various occupational hazards that are responsible for occurrences of different occupational injuries and diseases such as burn injury due to fire exposure, falling due to slips, fractures, and loss of body parts due to heavy and unsafe machinery, chemical poisoning due to exposure to different toxic substances, and suicidal ideation due to different psychosocial stressors. 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports showed that industries including the textile sector have various occupational hazards that are responsible for occurrences of different occupational injuries and diseases such as burn injury due to fire exposure, falling due to slips, fractures, and loss of body parts due to heavy and unsafe machinery, chemical poisoning due to exposure to different toxic substances, and suicidal ideation due to different psychosocial stressors. 16 , 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Reports showed that industries including the textile sector have various occupational hazards that are responsible for occurrences of different occupational injuries and diseases such as burn injury due to fire exposure, falling due to slips, fractures, and loss of body parts due to heavy and unsafe machinery, chemical poisoning due to exposure to different toxic substances, and suicidal ideation due to different psychosocial stressors. [16][17][18] In Ethiopia, several studies have been conducted on the prevalence and associated factors of occupational injuries among workers of textile and garment factors before the occurrence of COVID-19 with a 1-year prevalence of 40.8% among workers of Ayka Addis textile factory, 19 42.7% among Bahir Dar Textile factory, 20 31.4% among Arba Minch textile factory, 16 and 36.9% among Kombolcha textile factory. 12 Worldwide, there are inconsistencies regarding the prevalence of occupational injuries during the COVID-19 pandemic.…”
mentioning
confidence: 99%